Determinants of continuous intention to use online food delivery apps among generation y and z - Muhamad Irham, Ibrahim (2020)
Recent COVID-19 pandemic had driven an increasing trend on online food delivery apps usage. Such situation is observed as a positive development in the online business context. However, despite the interesting facts and figures on the projected revenue and growth of online food delivery apps usage around the globe, there were few customers' complaint recorded which could further interrupted overall usage of the apps in the future. Considering a huge amount of investment money made by the owner of the brand to develop the online platform and system, continuous usage of the apps perhaps could secure their long-run sustainability. Grounded by UTAUT theory and inclusive of trust in the recent model, this study attempts to examine on how the predetermined predictors that could contribute to the continuous intention of consumers to use online food delivery apps among generation Y and Z as typical users of the apps. A convenience survey among 410 online food delivery apps users in Kuala Lumpur revealed that performance expectancy, social influence, facilitating condition and trust have a significant influence on continuous intention to use online delivery apps among generation Y and Z. The findings of this study contribute in bridging the gaps of inconsistent results of the past studies and highlight the relevancy of trust in understanding UTAUT theory. Further, the results also suggest a few managerial implications for manager or owner of the brands to ensure their business sustainability. Besides, the future research direction of the study also discussed at the end of the thesis.